0516 Chinese Patients with Insomnia Recruited from Traditional Chinese Medicine (TCM) Hospital Successfully Treated With Telehealth Group CBT-I in Mandarin. (27th May 2020) - Xu, Y; Barwick, F; Li, C
Abstract: Introduction: Cognitive Behavioral Therapy for Insomnia (CBTI) is the recommended treatment for insomnia in the United States, Europe and China. Individual, group and online formats are effective, with moderate to large effect sizes in treatment outcomes. Although the prevalence of insomnia is 15% in China, most individuals do not seek CBTI and often prefer TCM. This study investigated whether CBTI delivered to Chinese in Mandarin via group telehealth showed similar outcomes compared to other countries. Methods: Chinese patients > 18 years with insomnia > 7 on the ISI were recruited from a sleep clinic in collaboration with Chongqing TCM Hospital in China. CBTI was delivered via 4-session telehealth group. Components included sleep education, sleep restriction, stimulus control, cognitive reframing, and relaxation. TCM use was extracted from medical records. Scores on self-report questionnaires assessing insomnia symptoms, sleep effort, sleep beliefs, and depression were compared pre- and post-treatment using paired sample t-tests with correction for multiple comparisons. Results: All patients (N=34) completed pre-post measures. Mean age was 44 years, sample was 82% female, and 91% had a bachelor or advanced degree. Average insomnia duration was 4.1 years, and 80% of sample used TCM during CBTI. Post-treatment outcomes showed significant decreases in insomnia symptoms (ISI Mdiff =4.0, SDdiff =6.4, p=.001, ES=.63), sleep effort (GSES Mdiff =2.3, SDdiff =3.2, p=.000, ES=.72), and unhelpful sleep beliefs (DBAS Mdiff =5.4, SDdiff =5.4, p=.000, ES=1.0), along with significantly lower depression symptoms (PHQ9 Mdiff =2.6, SD=3.8, p=.000, ES=.68) and improvement in daytime functioning (PSQI Mdiff .=0.6 SDdiff =1.2, p=.008, SE=.50). Medication use also decreased significantly (PSQI Mdiff =1.5 SDdiff =1.6, p=.000). Conclusion: Chinese patients with insomnia can be recruited successfully and treated effectively using CBTI via telehealth. Outcomes and effect sizes are similar to those seen with CBTI in other countries. Future comparison of CBTI with and without concurrent TCM could provide clinically relevant information. Support: None